The Effect of ICARE Learning Model on Students' Learning Outcomes in Physics Learning Class XI SMAN 13 Makassar - Jusriana, A (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2024)
The purpose of this research is to determine the learning outcomes of students who were taught using the ICARE learning model for class XI IPA SMAN 13 Makassar, to determine the learning outcomes of students who were not taught using the ICARE learning model for class students who were taught and those who were not taught using the ICARE learning model for class XI Science at SMAN 13 Makassar. The type of research used is quasi-experimental, using a research design only, non-equivalent control group design. This research consisted of 2 sample classes: 1 sample class as an experimental class, namely class XI IPA 1, totaling 35 students, and one other sample class as a control group, namely XI IPA 3, totaling 35 students. Researchers took one of the non-probability sampling techniques, namely convenience sampling. This research uses a learning outcomes test instrument. The results of the descriptive analysis in this research are students who were taught using the ICARE learning model for class and students who were not taught using the ICARE learning model for class. Meanwhile, after carrying out an inferential analysis in this research, it was discovered that there was a significant difference in the average learning outcomes between students who were taught and those who were not taught using the ICARE learning model in the effort and energy material of XI IPA students at SMAN 13 Makassar, based on the results of the Mann test calculations. Whitney (U) in SPSS 26, where the calculation results obtained a value of Zcount = 2.128 and Ztable = 1.96. These results show that Zcount > Ztable, so it can be concluded that Ho is rejected and H1 is accepted. This indicates differences in students' learning outcomes and those who need to be taught using the ICARE learning model for Class XI students at SMAN 13 Makassar.